Validation of an Abaqus impact wave propagation model - Bezes, P.D.D.; Grooteman, F.P.; Wiegman, J.W.E.; Marinho, N.R.; Loendersloot (My University, 2024)
A finite element model for wave propagation due to an impact is very desirable, to enable the design of optimal sensor network configurations for Structural Health Monitoring (SHM) applications, to obtain a better understanding of wave propagation (especially in composite structures) and also to generate simulated (virtual) test data for SHM algorithm development. Therefore, an Abaqus explicit finite element (FE) model was developed for wave propagation from impacts. To validate such a model, a series of impact tests were performed with a drop tower on an aluminium clamped square panel, at different impact energy levels and different impact locations. On the panel, eight FBG and six PZT sensors were installed. These experimental results were used to validate the FE model, in which the impacts were simulated and the computed. PZT and FBG sensor responses were compared against the experimental results. The paper will present the impact test setup, the finite element model and the validation results. The main focus of the paper will be the sensitivity analysis, identifying the model parameters that significantly affect the simulated impact sensor responses and their optimal settings. A good correlation between the numerical and experimental results was obtained.